Clinical Efficacy of Traditional Chinese Medicine, Suan Zao Ren Tang, for Sleep Disturbance during Methadone Maintenance: A Randomized, Double-Blind, Placebo-Controlled Trial - Chan, Yuan-Yu (Evid Based Complement Alternat Med, 2015)
Methadone maintenance therapy is an effective treatment for opiate dependence, but more than three-quarters of persons receiving the treatment report sleep quality disturbances. In this double-blind, randomized, controlled trial, we recruited 90 individuals receiving methadone for at least one month who reported sleep disturbances and had Pittsburgh Sleep Quality Index (PSQI) scores > 5. The purpose of this study was to determine whether Suan Zao Ren Tang, one of the most commonly prescribed traditional Chinese medications for treatment of insomnia, improves subjective sleep among methadone-maintained persons with disturbed sleep quality. Ninety patients were randomly assigned to intervention group (n = 45) and placebo group (n = 45), and all participants were analyzed. Compared with placebo treatment, Suan Zao Ren Tang treatment for four weeks produced a statistically significant improvement in the mean total PSQI scores (P = 0.007) and average sleep efficiency (P = 0.017). All adverse events (e.g., lethargy, diarrhea, and dizziness) were mild in severity. Suan Zao Ren Tang is effective for improving sleep quality and sleep efficiency among methadone-maintained patients with sleep complaints.